Abrasion of Teeth in Population Groups from Historical Periods in the Region of Former Yugoslavia - Dinka Mucić; Marija Đurić-Srejić (Dental Anthropology Association, 1996)
This study investigated the frequency, type, and degree of abrasion on permanent teeth from 694 skulls from archaeological sites dating from the beginning of the first century AD to the beginning of the twentieth century in the former Yugoslavia. The conclusions are: 1) 100% of the specimens had dental abrasion; 2) the Roman Age and Middle Ages teeth had a horizontal-vertical type of abrasion, while New Age teeth had a predominantly horizontal type of abrasion; and 3) Roman Age and the Middle Ages groups had the most severe loss of dental hard tissue.